The nanoscale architecture of force-bearing focal adhesions - Van Hoorn, Hedde; Harkes, Rolf; Spiesz, Ewa M.; Storm, Cornelis; Van Noort, Danny; Ladoux, Benoît; Schmidt, Thomas (Nano Letters, 2014)
The combination of micropillar array technology to measure cellular traction forces with super-resolution imaging allowed us to obtain cellular traction force maps and simultaneously zoom in on individual focal adhesions with single-molecule accuracy. We achieved a force detection precision of 500 pN simultaneously with a mean single-molecule localization precision of 30 nm. Key to the achievement was a two-step etching process that provided an integrated spacer next to the micropillar array that permitted stable and reproducible observation of cells on micropillars within the short working distance of a high-magnification, high numerical aperture objective. In turn, we used the technology to characterize the super-resolved structure of focal adhesions during force exertion. Live-cell imaging on MCF-7 cells demonstrated the applicability of the inverted configuration of the micropillar arrays to dynamics measurements. Forces emanated from a molecular base that was localized on top of the micropillars. What appeared as a single adhesion in conventional microscopy were in fact multiple elongated adhesions emanating from only a small fraction of the adhesion on the micropillar surface. Focal adhesions were elongated in the direction of local cellular force exertion with structural features of 100-280 nm in 3T3 Fibroblasts and MCF-7 cells. The combined measure of nanoscale architecture and force exerted shows a high level of stress accumulation at a single site of adhesion. © 2014 American Chemical Society.
CRIS-Team Scopus Importer:2024-02-19
Keywords: Cell mechanics; focal adhesion; mechanobiology; mechanosensing; super-resolution